PENGARUH KEGIATAN MARKET DAY TERHADAP KEMAMPUAN KERJA SAMA PADA ANAK USIA 4-5 TAHUN - Ashari, Dienda Nur Fitria; Reza, Muhammad; Sari Rakhmawati, Nur Ika; Fitri, Ruqoyyah (TARBAWI:Journal on Islamic Education, 2025)
This research is about the influence of activities market day on the ability to work together in children aged 4-5 years who have a background in which the ability to work together has not yet developed. In this case it is hoped that through activities market day Children can develop the ability to work together. The aim to be achieved in this research is to determine the influence of activities market day on the ability to work together in children aged 4-5 years. The research method used is a type of quasi-experimental research (nonequivalent pretest-posttest control group design) which was carried out at two institutions, namely Budi II Student Kindergarten as the experimental group and Aisyiyah Bustanul Athfal 50 Kindergarten as the control group with 15 students each. On test Mann Whitney U Test The results obtained were that in the initial ability test (pretest) There was no significant difference between the experimental and control groups regarding the ability to work together. And after giving treatment there were significant differences between the two groups. It was found that the experimental group had an increase. So it can be concluded that activities market day has an influence on the ability to work together in children aged 4-5 years.